Spaces on Ships: Secrecy and Privacy in the Dutch East India Companies - van Netten, Djoeke (TSEG - The Low Countries Journal of Social and Economic History, 2021)
Djoeke van Netten examines the interplay between privacy and secrecy in the ships of the Dutch East India Companies (1595-1799). Space aboard a ship was scarce and privacy a rare privilege. Netten starts with a discussion of the sources available as well as those lost to history. She then continues by examining what can be known about the protection of and access to (secret) information and (private) belongings aboard ships. Cases where privacy was violated and secrets revealed emerge as some of the most informative historical events to be examined in this context. As she confronts her historical examples with relevant theoretical and historiographical concepts, she concludes by raising important questions for further research on privacy and secrecy aboard ships.